The impact of Tubaramure, a food-assisted integrated health and nutrition program in Burundi, on children's development - Olney, Deanna K.; Leroy, Jef L.; Bliznashka, Lilia; Ruel, Marie T. (Wiley, 2015)
Tubaramure is a food‐assisted integrated health and nutrition program that targets pregnant women and their children up to 2 y of age (first 1000 d). Program beneficiaries received monthly food rations (corn‐soy blend and oil) and attended bi‐monthly nutrition and health education sessions and preventive health visits. We evaluated the program's impact over 2 y using a cross‐sectional cluster randomized controlled study. Sixty villages were assigned to one of 4 study groups that received benefits for different durations: T24: pregnancy up to 24 m; T18: pregnancy to 18 m; TNFP: same as T24, but without food rations during pregnancy; and Control. We estimated the program's impact on children's motor (30 milestones) and language (21 milestones) development in three age groups (4‐11 m, 12‐17 m and 18‐24 m).Tubaramure had statistically significant positive impacts on children's motor and language development although the pattern of impacts varied by age. The program led to higher achieved motor milestones among children aged 12‐17 m in the TNFP and T18 groups compared to control (1.2 and 0.8 milestones, respectively). No effect was found in T24. Tubaramure positively impacted language development among children 12‐17 m in the TNFP and T18 groups (0.9 and 0.8 milestones, respectively) and among children 18‐24 m in the T18 and T24 groups (0.8 and 1.6 milestones, respectively). There were no significant program impacts on motor or language development among children aged 4‐11 m. Tubaramure had a significant impact on motor development around the age when children obtain bipedal locomotion and on language development as they gain more language skills.Funded by USAID's Food and Nutrition Technical Assistance Project & CGIAR Research Program on A4NH, led by IFPRI.